Penyidikan Berbasis Ilmiah Dalam Penegakan Hukum Tindak Pidana Akses Ilegal - Rahman Amin; Agnes Anggraeni (Kajian Ilmu Kepolisian dan Anti Korupsi Universitas Bhayangkara Jakarta Raya, 2025)
Advances in science and technology have had an impact on the increase in types of crimes that are increasingly sophisticated and complicated so that they are difficult to uncover, one of which is the crime of illegal access. To overcome this, the Police developed science-based investigation techniques by utilizing science to uncover illegal access crimes. This research is a normative legal research with a legislative approach and a case approach to answer the problems raised. The results of the research, First, a scientific-based investigation was applied by the police by examining the fingerprint evidence of the perpetrator of the crime of illegal access to public service websites managed by the government as in the case of Cikarang District Court Decision Number 515/Pid.Sus/2021/PN.Ckr, and through forensic digital analysis to obtain electronic evidence on the device used by the perpetrator as per the Jember District Court Decision Number 17/Pid. Sus/2021/PN. Jmr, so that from the scientific-based investigation, the police succeeded in identifying and carrying out legal proceedings against the perpetrators and then a criminal verdict was handed down in court. Second, obstacles in science-based investigations, there are no specific provisions regulated in the Criminal Code, and the lack of number and quality of investigators who have the competence of scientific-based investigators, as well as the limitations of facilities and infrastructure to support science-based investigations in the Police unit at the regional level.